The Effect of Tax Avoidance and Sustainability Reporting on Company Value in Consumer Goods Sector Companies Listed on the Indonesia Stock Exchange in 2018 – 2022 - Novi Oktaviani; Tertiarto Wahyudi; Rela Sari (Cita Konsultindo Research Center, 2024)
The purpose of this study is to find out how tax avoidance and Sustainability Reporting have an impact on the value of companies in consumer goods companies listed on the IDX from 2018 to 2022. One type of quantitative research, this research tests hypotheses for each variable. This study uses sample withdrawal by purposive or authoritative sampling techniques; The number of company samples taken in this study was 31 companies, which had been observed for 5 years. This study uses quantitative data processed from the Indonesia Stock Exchange (IDX). Descriptive statistical tests, classical assumption tests, and hypothesis tests are used to test the hypothesis owned. The analysis was carried out using the IBM SPSS statistical program. The results of the study show that tax avoidance and good Sustainability Reporting can affect the value of a company. Thus, the existence of tax avoidance and good Sustainability Reporting in a company can affect good value for the company.